2019
DOI: 10.1111/ced.14034
|View full text |Cite
|
Sign up to set email alerts
|

British Association of Dermatologists ( BAD ) National Audit on Non‐Melanoma Skin Cancer Excision 2016 in collaboration with the Royal College of Pathologists

Abstract: Background. We conducted a re-audit of the surgical practice of UK dermatologists for the treatment of nonmelanoma skin cancer and examined changes with reference to our previous audit in 2014. The audit was supplemented by a detailed assessment of completeness of the histopathology reports for each tumour. Methods. UK dermatologists collected data on 10 consecutive nonmicrographic excisions for basal cell carcinoma (BCC) and 5 for squamous cell carcinoma (SCC). Data were collected on site, preoperative diagno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 15 publications
(18 reference statements)
0
14
0
Order By: Relevance
“…A total of 106 832 BCC and 21 569 SCC excisions were included. These were excised from 53 796 patients across all studies (25 studies did not report the number of patients, instead reporting the number of lesions only) 16,17,34,49,59,60,62,68,69,71‐74,78,81,95,103,106,108,111,114,119,131,133,134 . The mean (± SD) age of patients undergoing BCC excision was 67·4 (± 14·9 years) and for SCC excision was 70·9 (± 14·1 years).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of 106 832 BCC and 21 569 SCC excisions were included. These were excised from 53 796 patients across all studies (25 studies did not report the number of patients, instead reporting the number of lesions only) 16,17,34,49,59,60,62,68,69,71‐74,78,81,95,103,106,108,111,114,119,131,133,134 . The mean (± SD) age of patients undergoing BCC excision was 67·4 (± 14·9 years) and for SCC excision was 70·9 (± 14·1 years).…”
Section: Resultsmentioning
confidence: 99%
“…These factors would be best explored using Bayesian techniques. With SCC the margin used in different studies was infrequently reported in the larger studies 17,42,59,78,106,114,124,128 . When it was reported, several studies found no association between wider margins and reduced proportion of incomplete excision, 8,91 often as the deep margin was primarily affected 91 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of all skin lesions biopsied 45.5% of lesions occurred on the face reflecting the propensity for skin cancer to affect sunexposed sites. A recent British Association of Dermatologists National Audit on NMSC Excision also reported excisions from the head and neck to account for the majority (56.7%) of cases [22].…”
Section: Discussionmentioning
confidence: 99%
“…The figure of 5% incomplete excision with a 4-5-mm peripheral margin is therefore an estimation and not based on clinical evidence. Several previous large-scale studies such as two national audits of BCC and SCC excisions by UK dermatologists have reported an incidence of incomplete excision of between 2.3 and 3% [13,14]. There have been no previous systematic reviews on this topic.…”
Section: Systematic Review Registration: Prospero Crd42019157936mentioning
confidence: 99%